In the Shadow of Existence. Wisława Szymborska in Galician - Filipowicz-Rudek, Maria (Madrygal. Revista de Estudios Gallegos, 2019)
The article focuses on a deatailed analysis of the poetry of Wisława Szymborska, the Polish Nobel Prize winner, chosen and translated into Galician by Lucía Caeiro (Positivas, 2011), which includes different textual and metatextual aspects of the Polish original and its Galician version. The presented selection constitutes the first serious encounter between two literatures, and above all, two poetic traditions, confronting separate linguistic, literary and existential perceptions. This confrontation, however, leaves interesting conclusions about the dialogue between the two cultures, both at the level of semantic values (universal and local references) and at the quality level of poetic language (musicality, images, conciseness). An advanced reading, sometimes contrasted with different versions of Szymborska’s poems in other translations, allows us to formulate a thesis that the Galician version of the Polish poet creates a new poetic quality among a wide series of translations of Szymborska to the Iberian languages.